Karakteristik Morfo-Anatomi serta Kandungan Klorofil dan Kandungan Fitokimia Tanaman Ketul (Bidens pilosa) pada Tempat dengan Intensitas Cahaya yang Berbeda di Arboretum Universitas Padjadjaran - Karen Marcelline; Mohamad Nurzaman; Tia Setiawati (Pro-Life, 2025)
Bidens pilosa is a plant known for its secondary metabolites with therapeutic properties. This study aimed to examine the effects of different light intensities on the morphology, anatomy, chlorophyll content, and secondary metabolite production of B. pilosa in the Arboretum of Universitas Padjadjaran. The light intensity in the shaded area was 5,828 lux, while in the unshaded area, it was 32,768 lux. Leaf samples were collected from three individuals in each area, with three leaves taken per plant. Morphological and anatomical traits such as leaf thickness, leaf area, stomatal density, and chlorophyll content were observed, along with secondary metabolite content. Results showed that plants in the shaded area had thinner leaves (0,19 mm) and lower stomatal density (275.16 cells/mm2) but a larger leaf area (4 cm2) and higher chlorophyll content (29.33 CCI) compared to leaves in the unshaded area, which had thicker leaves (0.213 mm), higher stomatal density (310.83 cells/mm2), a smaller leaf area (2.33 cm2), and lower chlorophyll content (27.27 CCI). Alkaloids, flavonoids, tannins, and saponins were detected in both conditions, with a higher level of alkaloid and tannin in unshaded plants. This study provides insight into how light intensity affects plant morphology, photosynthesis, and secondary metabolite production, which could affect cultivation and medicinal applications. Further studies integrating additional environmental factors and quantitative analysis of secondary metabolites could provide a better understanding of these interactions.